Pengaruh Variabel Usaha dan Keterampilan pada Hubungan Insentif Moneter terhadap Kinerja - Budiarti, Laeli (JURNAL AKUNTANSI DAN AUDITING, 2013)
Previous researchs indicates that monetary incentives have a substantial impact on performance.This research investigates the effects of individual effort and skill on task performance. Theperformance of 71 managers of bank in Indonesia were examined. Using regression analysis,results obtained in this study showed that efforts has mediation effect, while skills has moderatoreffect on the relationship between incentives and managerial performance.